Advances in Rational Design and Materials of High‐Performance Stretchable Electromechanical Sensors. Issue 14 (26th February 2020) - Dinh, Toan; Nguyen, Thanh; Phan, Hoang‐Phuong; Nguyen, Tuan‐Khoa; Dau, Van Thanh; Nguyen, Nam‐Trung; Dao, Dzung Viet
Abstract: Stretchable and wearable sensor technology has attracted significant interests and created high technological impact on portable healthcare and smart human–machine interfaces. Wearable electromechanical systems are an important part of this technology that has recently witnessed tremendous progress toward high‐performance devices for commercialization. Over the past few years, great attention has been paid to simultaneously enhance the sensitivity and stretchability of the electromechanical sensors toward high sensitivity, ultra‐stretchability, low power consumption or self‐power functionalities, miniaturisation as well as simplicity in design and fabrication. This work presents state‐of‐the‐art advanced materials and rational designs of electromechanical sensors for wearable applications. Advances in various sensing concepts and structural designs for intrinsic stretchable conductive materials as well as advanced rational platforms are discussed. In addition, the practical applications and challenges in the development of stretchable electromechanical sensors are briefly mentioned and highlighted. Abstract : Stretchable electromechanical sensors that can monitor physical and mechanical stimuli generated by the human body are of considerable interest. The design of eletromechanical sensors based on appropriate rational structures and materials will enable the development of ultrasensitive and ultrastretchable sensing devices for human‐activity monitoring, portable healthcare, and smart human–machine interfaces.